2016
DOI: 10.17221/144/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water-restriction on various physiological variables in intensively reared Lacaune ewes

Abstract: ABSTRACT:The effects of water restriction on rectal temperature, respiratory rate and selected blood variables in intensively reared Lacaune ewes were evaluated. The tests were carried out over the course of 28 days in spring on 30 lactating sheep divided into three groups of 10 animals each, matched by lactation status and body weight and allocated into individual boxes. The animal groups were as follows: control group W100 with drinking water for the whole day (24 h/24 h), while the two experimental groups e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 47 publications
(71 reference statements)
8
27
1
3
Order By: Relevance
“…Although plasma/serum volume was not measured during the study, previous studies have shown the relevance of serum osmolality in determining the dehydration status of small ruminants [29,43]. The observed higher serum concentration of total proteins in water-restricted lambs might help in maintaining the blood oncotic pressure in water-stressed animals as the loss of water results in hemoconcentration and hypovolemia [53]. It is interesting that the observed lower DMI herein due to water restriction did not result in a decreased serum concentration of total proteins, as previously reported in ewes [18,54].…”
Section: Discussionmentioning
confidence: 95%
“…Although plasma/serum volume was not measured during the study, previous studies have shown the relevance of serum osmolality in determining the dehydration status of small ruminants [29,43]. The observed higher serum concentration of total proteins in water-restricted lambs might help in maintaining the blood oncotic pressure in water-stressed animals as the loss of water results in hemoconcentration and hypovolemia [53]. It is interesting that the observed lower DMI herein due to water restriction did not result in a decreased serum concentration of total proteins, as previously reported in ewes [18,54].…”
Section: Discussionmentioning
confidence: 95%
“…The need to effectively utilise the limited water within the animal's body normally results in increased water reabsorption; consequently, urea is increasingly reabsorbed (nephron level) giving its high permeability (Hamadeh et al 2006). Other water restriction studies in goats (Alamer 2006;Abdelatif et al 2010) and sheep (Jaber et al 2004;Casamassima et al 2016) reported increased urea concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…La privation d'eau de 25 % a augmenté significativement les concentrations sériques en protéines totales et en créatinine chez les chèvres Arbia, comparativement à l'hydratation normale. Plusieurs auteurs ont noté une augmentation des deux paramètres lors d'une épreuve de déshydratation, notamment Eltayeb (2000) chez les chèvres Nubiennes, Alamer (2005) chez des chèvres d'Arabie Saoudite, Aganga et al (1988) chez des caprins Maradi, et Casamassima et al (2016) chez des brebis Lacaunes. Cependant, une augmentation modérée du taux de créatinine plasmatique a été observée après trois jours de restriction hydrique chez le mouton Barki (Abdelatif et Ahmed, 1994).…”
Section: Paramètres Plasmatiques Du Métabolisme Azotéunclassified
“…Dans notre étude, la salinité de l'eau d'abreuvement n'a pas eu d'effet significatif sur le niveau de glucose plasmatique chez les caprins de race locale, comme rapporté par Eltayeb (2000) chez des chèvres Nubiennes. D'autres auteurs ont fait le même constat chez les ovins (Casamassima, 2016) Dans la présente étude, l'urémie a été significativement influencée par la restriction hydrique. Ainsi, les animaux du lot 4, partiellement privés d'eau d'abreuvement, ont présenté des valeurs d'urée sérique significativement supérieures à celles des autres lots.…”
Section: Paramètres Plasmatiques Du Métabolisme éNergétiqueunclassified
See 1 more Smart Citation